Impact of baffle geometry on the fluid motion in the stirred vessel - Młynarczykowska Anna; Ferrari Simone; Demurtas Luana; Jaszczur Marek (EPJ Web of Conferences, 2022)
The fluids mixing is a crucial operation in a large number of engineering systems. It has major significance in chemical engineering, food, cosmetics and pharmaceutics production, biotechnology, wastewater treatment engineering, and countless other applications. Among many available systems online mixing with static mixers and stirred tanks plays a primary role and has been developed to meet several processing objectives. The effectiveness of the mixing process depends on a number of parameters, i.e. impeller shape, mixing phases properties, process conditions as well as stirred vessel design - in particular, number and baffles’ design. The optimal baffles geometry is still an open issue and is usually design with trial and error methods. In this study, the focus is on the experimental investigations of the baffle geometry on the fluid flow and mixing phenomenon as well as on the required by the mixer power. In order to evaluate velocity field and mixing parameters, particle image velocimetry measurement is used whereas to obtain the power consumption by the stirred vessel precise torque meters were used. Measurements are carried out for different Reynolds numbers, to determine the most efficient process parameters. It has been shown that for the analyzed range of Reynolds numbers, the baffles design significantly influences fluid flow motion, mixing phenomena and the pumping number power number, but not affect the power number.